Effects of Four Imported Floating Diets on Feed Intake and Daily Feeding Rate of Grass Carp, Ctenopharyngodon idella (Valenciennes, 1844). - Sadiq Jwad Muhammed (University of Thi-Qar Journal of agricultural research, 2024)
The present study was conducted in the laboratories of the Aquaculture Unit, College of Agriculture, University of Basra, to determine the effect of four imported floating feeds (Arabco, Aleer, Arasco and Grand).Feed intake as well as the daily rate of. Twelve glass aquarium were used, with four treatments and three replicates for each treatment. The average weight of the experimental fish was 50.62 ± 2.61 g. The experimental fish were brought from Al-Bahaa Fish Farm located in Abi Al-Khaseeb District, south of Basra City, Iraq. The results showed that the daily feed intake was 12.40, 16.53, 14.50 and 12.31 g. and the daily feeding rate was 0.12, 0.17, 0.15 and 0.12 g. for grass carp fed floating diets from Arabco, Aller, Arasco and Grand, respectively. The statistical analysis's results showed that there were significant differences (P ≤0.05) in the in the daily feed intake of grass carp fed floating diets from Arabco, Arasco, Grand, and Arasco from Aller, The floating diets of Grand and Arabco were not different significantly (P > 0.05). with. the floating diets of Arabco and Grand..